Sales and Distribution Management. - Panda, Tapan K; Sahadev, Sunil (Oxford : Oxford University Press, 2006)
"Sales and Distribution Management is a composite and comprehensive textbook specially designed to meet the requirements of MBA students specialising in marketing. Users will find this book highly useful for its coverage of sales and sales force management, the sales organisation and territory management, designing a distribution system and distribution management - explained through caselets, diagrams, flowcharts and numerous examples from the Indian context
Keywords: Sales management; Marketing channels; Physical distribution of goods; Marketing channels -- Management; Physical distribution of goods -- Management